Performance Analysis on Dual-band Annular Ring Microstrip Antenna at 1.9 GHz and 2.1 GHz Operating Frequencies - Cahya Adi Kuncara; Yuyun Siti Rohmah; Dwi Andi Nurmantris; Radial Anwar (IJAIT (International Journal of Applied Information Technology), 2018)
Annular ring antenna concept has been utilized in many applications. This paper presents the adoption of annular ring concept on a dual-band microstrip antenna. The antenna is designed to operate at 1.9 GHz and 2.1 GHz operating frequencies. The objective of this research is to observe the method potential of combining two patches operate at different frequencies as a single dual-band antenna. While the purpose of the annular concept is to enhance the bandwidth of an antenna, analysis from this work shows that for a dual-band antenna with operating frequencies close one to the other, the obtained bandwidths are relatively narrow, down to of about 5%. Nevertheless, the antenna is capable to operate at both designated frequencies with good return losses down to -24.40dB.